2000
DOI: 10.3402/tellusb.v52i3.17075
|View full text |Cite
|
Sign up to set email alerts
|

Model analysis of the influence of gas diffusivity in soil on CO and H<sub>2</sub> uptake

Abstract: CO and H 2 uptake by soil was studied as a diffusion process. A diffusion model was used to determine how the surface fluxes (net deposition velocities) were controlled by in-situ microbial uptake rates and soil gas diffusivity calculated from the 3-phase system (solid, liquid, gas) in the soil. Analytical solutions of the diffusion model assuming vertical uniformity of soil properties showed that physical properties such as air-filled porosity and soil gas diffusivity were more important in the uptake process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 33 publications
2
54
1
Order By: Relevance
“…Their model was able to capture the observed vertical profiles of H 2 in the soil and showed that the thickness of the inactive layer is important for a realistic simulation of the flux strength. In this study, we incorporate the same type of 1-D diffusion model described in Yonemura et al (2000a) to the deposition scheme of the CHASER model.…”
Section: Soil Uptake Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Their model was able to capture the observed vertical profiles of H 2 in the soil and showed that the thickness of the inactive layer is important for a realistic simulation of the flux strength. In this study, we incorporate the same type of 1-D diffusion model described in Yonemura et al (2000a) to the deposition scheme of the CHASER model.…”
Section: Soil Uptake Modelmentioning
confidence: 99%
“…The inactive layer acts as a diffusion barrier, and is probably caused by the dryness and high temperature near the ground surface. Yonemura et al (2000a) calculated the deposition velocity of H 2 using a 2-layer diffusion model that incorporated the biologically inactive and active layer. Their model was able to capture the observed vertical profiles of H 2 in the soil and showed that the thickness of the inactive layer is important for a realistic simulation of the flux strength.…”
Section: Soil Uptake Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, eq. (1) can be used to describe the dependence of v d on U w and T. This description is more complete and more realistic than that derived from the onelayer model used so far (Yonemura et al, 2000;SmithDowney et al, 2008;Morfopoulos et al, 2012). Yet, eq.…”
mentioning
confidence: 99%
“…The two-layer model was first suggested by Yonemura et al (2000), and it assumes uniform conditions in the respective layers. d is the depth of the dry top layer, D S is the diffusivity of H 2 in the soil (D S,I in the dry top layer, D S,II in the moist, deeper soil layer), k s is the rate constant for removal of H 2 from soil air, and U a is the fraction of soil volume filled with air.…”
mentioning
confidence: 99%